A study on awareness and attitude towards maintenance of oral health and hygiene in women of reproductive age group of Rewa (M.P.) - Divashree Sharma; Ambrish Mishra; Beenu Kushwah; Manoj Saxena (International Journal of Medical Research and Review, 2015)
Aim: To assess the oral health knowledge, oral hygiene habits, attitude towards maintenance of oral health, and the periodontal health status of women of reproductive age group (15 to 45 years) in Rewa.Materials and methods: The awareness and attitude of 80 pregnant and 80 non-pregnant women reporting to the outpatient department of Government hospital of Medical College in Rewa over a period of 2 months (May -June 2015) towards maintenance of oral health was assessed with a close ended questionnaire. The periodontal health of women was evaluated by Community Periodontal Index (CPI).Results: There was a significant difference in the periodontal status (mean CPI score) among both groups of women (p< 0.05).Conclusion: The awareness among women towards oral health related issues is poor. There is lack of awareness about about safe medical and dental care practices during pregnancy. Community Periodontal Index (CPI) tended to be higher in pregnant than in non-pregnant women, suggesting a poorer oral health status in pregnancy.